The effectiveness of injury prevention programs to modify risk factors for non-contact anterior cruciate ligament and hamstring injuries in uninjured team sports athletes: A systematic review - Monajati, A.; Larumbe-Zabala, E.; Goss-Sampson, M.; Naclerio, F. (PLOS ONE, 2016)
Background: Hamstring strain and anterior cruciate ligament injuries are, respectively, the most prevalent and serious non-contact occurring injuries in team sports. Specific biomechanical and neuromuscular variables have been used to estimate the risk of incurring a non-contact injury in athletes.